PEMIKIRAN EKONOMI YAHYA BIN UMAR DALAM PERSPEKTIF EKONOMI MODERN - Mohammad Subhan (LP2M IAI Miftahul Ulum Pamekasan, 2015)
Islam as a religion has given some rules of human live, whether it deals with hablum minallah, hablum minannas and social environment. The rule of hablum minallah is static while the rule of hablum minas and social environment are dynamic and flexible. In other words, human is given an authority to make the rules based on the situation and condition era, Basically, this article explains the economic theory of Yahya bin Umar in his book Ahka>m al-suq . generally this book explains about hisbah and other topic related to the market like al-ta’sir (pricing), ihtikar , siyasah al-ighraq (dumping). In this article the author tries to correlative study about Yahya bin Umar idea in Ahkam sl-suq book with economic conventional theory. And then it will be known whether the brilliant idea of Yahya bin Umar still relevant in this era